2019
DOI: 10.1128/aem.00762-19
|View full text |Cite
|
Sign up to set email alerts
|

NfiR, a New Regulatory Noncoding RNA (ncRNA), Is Required in Concert with the NfiS ncRNA for Optimal Expression of Nitrogenase Genes in Pseudomonas stutzeri A1501

Abstract: Expression of nitrogenase genes (nifHDK) is strictly regulated at both transcriptional and posttranscriptional levels. Efficient nitrogenase activity requires maintaining sufficient levels of nif mRNAs, yet the underlying mechanism is not fully understood due to its complexity. We have previously shown that a novel regulatory noncoding RNA (ncRNA), NfiS, optimizes nitrogen fixation through targeting nifK mRNA in Pseudomonas stutzeri A1501. Here, we report the identification and characterization of a second ncR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…The amplification conditions of the qRT-PCR assays were as follows: 95 • C for 5 min, followed by 40 cycles of 95 • C for 30 s, 60 • C for 1 min, and 72 • C for 30 s and then a dissociation curve analysis. The 16S rRNA gene was used as the endogenous reference gene to normalize the expression of target genes in each cDNA template [23]. The relative expression level of target genes was calculated by the comparative threshold cycle (2 −∆∆Ct ) method.…”
Section: Rna Isolation and Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%
“…The amplification conditions of the qRT-PCR assays were as follows: 95 • C for 5 min, followed by 40 cycles of 95 • C for 30 s, 60 • C for 1 min, and 72 • C for 30 s and then a dissociation curve analysis. The 16S rRNA gene was used as the endogenous reference gene to normalize the expression of target genes in each cDNA template [23]. The relative expression level of target genes was calculated by the comparative threshold cycle (2 −∆∆Ct ) method.…”
Section: Rna Isolation and Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%
“…Coleman and coworkers described the first evidence of a functional sRNA of bacterial origin with the characterization of micF, a non-coding RNA complementary to the Shine-Dalgarno sequence of the E. coli lpp mRNA that was able to silence its expression [28]. Bacterial sRNAs belong to two functional families: the cisRNAs originated by antisense transcription of coding genes that act over the parental coding frames by complementary base pairing and they are generally involved in processes, such as the maintenance of the copy number in plasmids or the regulation of operons [29] and the trans-encoded sRNAs that are generated by specific transcriptional units and involved in the post-transcriptional regulation of mRNAs [30]. Moreover, the recent developments of next-generation sequencing approaches for transcriptomic analysis allowed for the characterization of new populations of bacterial sRNAs derived from the post-transcriptional processing of other RNAs [26].…”
Section: Diversity Of Rna Species In Transcriptomic Outputmentioning
confidence: 99%
“…have to adapt to nutrient deficiency. In Pseudomonas, NtrC positively regulates the transcription of σ54-dependent target genes under low nitrogen conditions, including the expression of glnA (Hervás et al, 2009) and rhlA (Wenner et al, 2014;Pita et al, 2018), nitrate assimilation operon (Romeo et al, 2012), and nitrogenase genes (Zhan et al, 2019). We observed that mRNAs of nahU (salicylate hydroxylase) and catA (catechol 1,2-dioxygenase) were down-regulated at decreasing NH 4 Cl concentration from 5 to 1 mM, the rpoD mRNA level remained unchanged, but the ihfA mRNA level altered.…”
Section: Discussionmentioning
confidence: 80%